Analysis and future outlook of intra-Asia shipping - Chang, Wenxian (2018)
Benefited from the fast developing economy, the container shipping market in Asia is steadily growing these years. The intra-Asia trade has become the world’s largest container shipping market. One out of four containers is on the intra-Asia trades and the share is still increasing. In 2017, the world’s top 10 busiest containers ports are all from Asia. It is estimated that in 2018 the intra-Asia container trade volume will exceed 30 million TEUs.